Politics, the military, and national security in Jordan, 1955-1967 - Tal, L; Tal, Lawrence (1997)
This study argues that the Hashemite Kingdom of Jordan survived the years between the signing of the Baghdad Pact in 1955 and the outbreak of the June 1967 war due primarily to the cohesion of its National Security Establishment (NSE), a ruling coalition of security and foreign policy professionals from the monarchy, the political elite, and the military. By examining the national security policymaking process in Jordan between 1955 and 1967, this study shows that NSE members often disagreed over the means of protecting Jordanian national security, but agreed on the ultimate end of security policy: the preservation of the Hashemite monarchy and the protection of the territorial integrity of Jordan. This thesis examines in detail the foreign and domestic challenges to Jordanian national security during the kingdom's most turbulent period. The thesis makes extensive use of primary sources from the British, American, and Jordanian archives, Arabic and English language memoirs, and interviews with surviving Jordanian decisionmakers. In addition, the study builds on the work of previous scholars by making use of the published literature on Jordan. The first three chapters are organised thematically, while the remaining chapters are organised chronologically.